Sustainable Development of a City: Systemic Approach - Mierzejewska, Lidia (Problemy Ekorozwoju, 2017)
Today the concept of sustainable development has been adopted as a basis for promoting development at all levels of territorial organisation. While generally worked out for the global level, this conception has also attained a local dimension, after the local Agenda 21 had been drawn up at the Rio conference in 1992. However, each level of development planning has its own specific features, and so have individual territorial units at that level. This also, or perhaps primarily, concerns cities because of wide differences in their sizes, the complexity of relations occurring there, the accumulation of development problems, the special role they play in the settlement system and difficulties with transferring the assumptions of a conception worked out for the global scale to the local level. This paper seeks to find a way of understanding sustainable development appropriate to the specificity of a city, with special attention paid to a systemic conception, and more specifically that of a territorial social system. Also, an analysis is made of selected conceptions and models indicating concrete measures that should be taken to make urban development more balanced, especially in its spatial aspect. The reflections lead to the conclusion that sustainable urban development can hardly be associated with the sustainability presented in the report Our Common Future; rather, it should involve a search for conditions of a city’s intra- and inter-system balance and relations with its immediate and farther vicinity.